(untitled) (The Review of Diabetic Studies, 2023)
The results of a number of large trials and the arrival of new glucose-lowering drugs are changing the scene of diabetes care in patients with type 2 diabetes. The results of the ADVANCE and ACCORD trials have shown that strict glycemic control does not improve macrovascular outcome. Consequently, the importance of duration of disease, presence of cardiovascular disease and risk of hypoglycemia, have been brought again into focus as considerations in designing individual treatment plans. New drugs related to the incretin system have emerged in the past year, and these may decrease certain risks of classic glucose-lowering drugs. However, we have to be aware of the possibility of yet unknown longer-term risks from newly developed drugs. The new insights from the trials presented on the EASD meeting 2008 and the emerging information on the new drugs are used in this paper to start defining the contours of prospective new treatment strategies.